The Use of Glycolic Acid for Aesthetic Skin Renewal - Jurkėnaitė, Milena; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2022)
Acids such as chemical peels effectively improve the condition of the skin, inhibit inflammatory processes. The aim – to determine the effect of cosmetic products with glycolic acid on facial skin. Method. An unstructured interview was conducted during qualitative research. Two study participants were selected in the target selection: 1st participant (29 years old), 2nd participant (22 years old). The client card was filled in, a course of glycolic acid procedures was performed individually, with a frequency of every 10 days. Photos were taken before and after each procedure to evaluate skin changes, all the data was archived and analyzed. Results. A mixed skin type was identified for the first study participant, keratinization, fine facial wrinkles, scars after acne, yellowish skin tone. Oily skin type was identified on the second study participant, map of papules and pustules on the cheek areas, comedones on the nose and chin. For the first participant glycolic acid treatments reduced the relief of mimic wrinkles, restored skin moisture, decreased comedones, and did not cause new rashes. In the case of second participant, glycolic acid reduced comedones, inflamed areas of the skin, lightened scars. The facial skin of both participants looked visually refreshed, brighter and smoother. Conclusion. 1. The positive effect of glycolic acid was observed on each participant. Among the treatments, glycolic acid-containing cosmetics were used to maintain the condition of the facial skin at home. 2. Visually observed aesthetic skin changes: first participant’s skin regained moisture, smoothened with decreased comedones. Second participant’s skin had a reduction in rashes, inflamed areas of the skin and comedones, also lightened scars.